An assessment of factors associated with thickness of the endometrium in postmenopausal women - Sobczuk, Anna; Wrona, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
The aim of this study was to demonstrate an association between thickness of the endometrium measured by transvaginal ultrasound and factors known to be associated with oestrogen exposure: accompanying diseases (ischaemic heart disease, arterial hypertension, osteoporosis, obesity), serum hormone levels (FSH, E2) and other factors such as age, time since last menses, smoking, and use of hormone replacement therapy in the past in postmenopausal women. The study included 92 patients between 46 and 66 years. Statistically significant associations between thickness of the endometrium and use of HT in the past were not seen. In smokers a statistically significant relationship between level of plasma oestradiol and thickness of the endometrium was noticed. In our study there was no significant influence of smoking on thickness of the endometrium. There was no statistically significant correlation between thickness of the endometrium and plasma levels of cholesterol, triglycerides and glucose. Also adiposity, arterial hypertension and diabetes mellitus did not increase endometrial thickness.